Speech Perception Triggers Articulatory Action: Evidence From Mechanical Stimulation - Berent, Iris; Platt, Melanie; Theodore, Rachel; Balaban, Evan; Fried, Peter J.; Pascual-Leone, Alvaro (Frontiers in Communication, 2020)
Neuroimaging studies show that the brain articulatory motor system is activated during speech perception. These results, however, cannot determine whether the motor system is engaged in motor simulation (e.g., lip movement) or in non-motor computations. To gauge the causal role of the articulatory motor system, here we examine the effect of mechanical stimulation. Participants heard speech tokens, ambiguous with respect to voicing—either labial (ba/pa) or coronal (da/ta)—while lightly biting on either the lips or tongue. Compared to incongruent stimulation (e.g., lips, with da/ta), congruent stimulation (e.g., tongue, with da/ta) shifted the voicing percepts and improved discrimination sensitivity (d’). Results are the first to demonstrate that adults engage the articulatory motor system in speech perception even when it is irrelevant to response. The convergence with transcranial magnetic stimulation experiments demonstrates that speech perception engages articulatory action. These conclusions illuminate the links between embodiment and cognition.